Pengaruh Kompetensi Kepribadian dan Kompetensi Sosial terhadap Pelaksanaan Supervisi Akademik Pengawas Sekolah Menengah Atas - Triyanto Pristiwaluyo; Fatimah Ab Hakim (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2018)
This study aims to determine personality competence, social competence and academic supervision of high school supervisors as well as the influence of personality and social competencies on the implementation of academic supervision conducted by high school supervisors. The type of research is ex post facto research. The study population was all permanent teachers with the status of civil servants (PNS) in State High Schools in Luwu Regency. The study sample consisted of 152 teachers obtained by the proportional simple random sampling technique. The data of this study were collected using the personality and social competency instruments of the supervisor and the implementation of academic supervision in the form of questionnaires with a Likert scale model. The data analysis technique used is descriptive analysis and multiple regression analysis. The results of the study indicate that: (1) the competence of personality and social competence of high school supervisors is in the very high and high category, and the implementation of supervisory academic supervision in high schools is in the good category. (2) The supervisory personality and social competencies in high school together have a positive effect on the supervisory academic supervision, and (3) Personality competency and supervisory social competence each have a positive influence on the implementation of supervisory academic supervision in high school.